2012
DOI: 10.1016/s0924-9338(12)75331-2
|View full text |Cite
|
Sign up to set email alerts
|

P-1164 - Transference and countertransference in cognitive behavioral therapy

Abstract: Both patients and psychotherapists can experience strong emotional reactions towards each other in what are termed transference and countertransference within therapy. In the first part of this review, we discuss transference issues. Although not usually part of the obvious language of cognitive behavioral therapy (CBT), examination of the cognitions related to the therapist, is an integral part of CBT, especially in working with difficult patients.MethodsPUBMED data base was searched for articles using the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the second study with an ineffective intervention 16 , the intervention was delivered by nurses who had only completed two days of CBT training, which may have contributed to the limited results of the intervention. Studies have shown that both the therapeutic alliance and therapist competence are related to therapy outcomes 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second study with an ineffective intervention 16 , the intervention was delivered by nurses who had only completed two days of CBT training, which may have contributed to the limited results of the intervention. Studies have shown that both the therapeutic alliance and therapist competence are related to therapy outcomes 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant reduction in HbA1c in two of the three studies 20 , 23 , and no reduction in HbA1c in the third study 16 . As mentioned earlier, the intervention in this study was delivered by nurses who had only completed two days of CBT training, and a lack of therapist competence may contribute to ineffective interventions 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%